IMPROVING THE PRACTICE OF BUSINESS PLANNING IN THE INDUSTRIAL ENTERPRISE - MALTUZ, Viktoriya; MALTUZ, Оleksander (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to the study of directions for improving the practice of business planning in domestic industrial enterprises. The content of the concept of "business planning" is considered. Taking into account the fact that business planning combines elements of strategic and operational planning, and one of its most important tasks is to focus attention on key tasks that lead to the success of the enterprise, the development of strategic maps is proposed as a tool for improving the practical aspects of business planning, and a strategic card for PrJSC "Ukrhydroenergo". The feasibility of introducing a system of compliance control of business processes at domestic enterprises using a risk-oriented approach, which aims to minimize the risk of legal and regulatory sanctions, antimonopoly prosecution, financial losses or loss of reputation as a result of the enterprise's failure to comply with legislative acts, market standards, as well as standards and internal documents of the enterprise itself. The methodology of step-by-step integrated business planning is considered as an alternative to traditional methods of business planning. Automation (computerization) of the business planning system, which makes it possible to create several types of plans, is also proposed as a means of improving the business planning system at an industrial enterprise; standardization, which will allow optimizing the parameters of building a business planning system, unifying its excessively diverse components.
Keywords: business planning; strategic map; compliance control; business process; risk management; business planning methods; automation; standardization